EPALE Community Stories – As a source of inspiration for adult educators - Świtalski, Wojciech (Difficult situation in biographies: Volume 9, 2025)
The author describes an initiative undertaken on the electronic platform EPALE. The initiative is called EPALE Community Stories. It consists of publishing biographical experiences of adult educators from all over Europe. The materials posted on EPALE were the source of analysis, in which the following questions were asked. What is the purpose of EPALE Community Stories? What is the structure of EPALE Community Stories? Who is the hero of EPALE Community Stories? What do EPALE Community Stories tell? What response do EPALE Community Stories evoke among readers? The answers obtained allowed us to conclude that EPALE Community Stories are a source of biographical inspiration for adult educators.